Assessment of Nurses' Practice of Standard Precautions in Hospitals of Babil Governorate, Iraq - Mustafa Hasan; Wissam Abdul-Ameer Ali; Rajaa Ahmed Mahmoud (Shiraz University of Medical Sciences, 2024)
Background: Hospital-acquired infection (HAI) is one of the most frequent issues that hospitals are faced with in every country worldwide. Nurses are an essential part of the medical workforce that play a special role in preventing the transmission of infections within hospitals by implementation of infection prevention standard precautions. This study aimed to assess the level of nurses' practice regarding standard precautions.Methods: 400 nurses from eight hospitals in Babil governorate are included in this cross-sectional study. To assess the knowledge and practice levels, was used an interview questionnaire. SPSS- 27 was used to analyze the data collected from September 2022 to March 2023.Results: Among 400 nurses, the mean age was 29.07 years and a large number of them (43.8%) had a diploma; while most of nurses had less than 5 years of work experience, the main result revealed that 51.5% of them had poor practice regarding standard precautions.Conclusion: The majority of nurses did not always practice these precautions, so there is a need to hold educational courses and training workshops for nurses to improve their practice of these measures.